Dumai Convention Dan Exhibition Center Dengan Pendekatan Arsitektur High-Tech - Saputra, Aldino Harli; Hidayat, Wahyu; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The Dumai City always make an exhibition event for every years called Dumai Expo that to celebrate Dumai City's birthday. Besides Dumai Expo event, there are also other events that held such as religious events, gatherings of important people, music festivals, cultural festivals, performances, and many other. Therefore, the Convention and Exhibition Center will be a place that can be used to accommodate those events. The method in this design is to use the High-Tech Architecture approach by applying all its characteristics. The concept that used is Celebration of Unity, obtained from the design functions and themes. The application of the concept on this design is divided into two part namely Celebration on the buildings and Unity on landscape design.Key word: Convention, Exhibition, High-Tech Architecture